STRATEGI PENINGKATAN SUMBER DAYA MANUSIA DI BIDANG KEPARIWISATAAN DI DESA WISATA SUKAMANDI, KECAMATAN SAGALAHERANG, KABUPATEN SUBANG - Rajoendah, Muhammad Iqbal Katik; Anggraini, Asterina; Syafganti, Imam; Wardhani, Annisa; Rudatin, Christina Lipuringtyas; Akbar, Djuni (STAI Darul Qalam Tangerang, 2025)
The primary issues addressed in the community service initiative in Sukamandi Tourism Village, Sagalaherang District, Subang Regency, are the lack of understanding regarding sustainable tourism village management and the role of tourism awareness groups (pokdarwis), as well as the inability to utilize social media for promotion. The objective of this initiative is to enhance the quality of human resources in the tourism sector to support sustainable tourism village management and the use of social media for village tourism promotion. The method employed is Participatory Action Research (PAR), which involves stages of survey, coordination with village government, training, and evaluation. The training results indicate a significant improvement in participants' understanding of sustainable tourism village management, the role of pokdarwis, UMKM product packaging, and social media promotion strategies. This initiative is expected to encourage the development of sustainable tourism in Sukamandi Village, improve economic welfare, and preserve local culture and the environment.